Mechanisms and Role of Nitric Oxide in Phytotoxicity-Mitigation of Copper - Rather, Bilal A.; Masood, Asim; Sehar, Zebus; Majid, Arif; Anjum, Naser A.; Khan, Nafees A. (Frontiers in Plant Science, 2020)
Phytotoxicity of metals significantly contributes to the major loss in agricultural productivity. Among all the metals, copper (Cu) is one of the plant-beneficial heavy metals, however, it exhibits toxicity at its supra-optimal level. Cu affects plants from initiation of seed germination to the senescence and was found to impact photosynthetic functions, growth, and productivity. The use of plant growth regulators, phytohormones and other signaling molecules are among the major approaches for combatting Cu toxicity in plants. Nitric oxide (NO) is a versatile and essential bioactive gaseous signaling molecule. It is involved in various plant’s physiological and molecular processes. NO also modulates plant responses to multiple stress factors including elevated Cu levels. Literature available in this context is centered mainly on the role of NO in combating Cu stress with partial discussion on underlying mechanisms. Considering recent reports, this paper: (a) overviews Cu uptake, transport; (b) recent updates highlighting the major aspects of Cu-toxicity on germination, photosynthesis, growth and nutrient-use-efficiency; (c) update on NO as a signaling molecule; and (d) critically appraises the Cu-significance and mechanisms underlying NO-mediated alleviation Cu-toxicity in plants. The outcome of the discussion may provide important clues for future research on NO-mediated mitigation of Cu-phytotoxicity.